A new role for e-beam electron projection. - Harriott, L.R (IEEE spectrum)
In the Scalpel system, a wide beam of electrons replaces light as the means of wafer exposure, and throughput is aided by a step-and-scan approach. One of the leading candidates for next generation lithography is Scalpel, which stands for scattering with angular limitation projection electron-beam lithography. Scalpel is a reduction image-projection technique that relies on 100 keV electrons and the contrast caused when they are scattered. The use of electrons gets round the diffraction limitation of optical lithography. The mask consists of a membrane with a low atomic number, covered with a layer of material with a high atomic number, in which the pattern is delineated. The mask is almost completely transparent to electrons at 100 keV, but contrast is generated from the difference in electron scattering characteristics between the membrane and patterned material. The membrane scatters electrons weakly and to small angles, while the patterned layer scatters them strongly and at large angles. An aperture in the back-focal plane (pupil) of the projection optics blocks the strongly scattered electrons, forming a high-contrast aerial image at the wafer plane. The functions of contrast generation and energy absorption are thus divided between mask and aperture. This division of labor means that very little of the incident energy is actually absorbed by the mask, which therefore is almost immune to thermal instabilities